2022
DOI: 10.3390/s22176416
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Two-Dimensional Surface Displacements Using High-Resolution Cosmo-SkyMed, TerraSAR-X and Medium-Resolution Sentinel-1 SAR Interferometry: Case Study for the Tengiz Oilfield

Abstract: The present study was aimed at comparing vertical and horizontal surface displacements derived from the Cosmo-SkyMED, TerraSAR-X and Sentinel-1 satellite missions for the detection of oil extraction-induced subsidence in the Tengiz oilfield during 2018–2021. The vertical and horizontal surface displacements were derived using the 2D decomposition of line-of-sight measurements from three satellite missions. Since the TerraSAR-X mission was only available from an ascending track, it was successfully decomposed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
1
3
1
Order By: Relevance
“…Furthermore, the mean velocity per grid reveals deformation rates ranging from −8.61 mm/year to 9.40 mm/year if quadrants with noisy points (areas near water resources) are eliminated. This deformation rate shows be lower when compared to deformational findings from other studies conducted in oil fields areas [3,43,44].…”
Section: Discussioncontrasting
confidence: 71%
“…Furthermore, the mean velocity per grid reveals deformation rates ranging from −8.61 mm/year to 9.40 mm/year if quadrants with noisy points (areas near water resources) are eliminated. This deformation rate shows be lower when compared to deformational findings from other studies conducted in oil fields areas [3,43,44].…”
Section: Discussioncontrasting
confidence: 71%
“…The multi-temporal coherence of the PS-InSAR measurements derived from SNT1 was higher than from CSK. Higher temporal decorrelation of X-band CSK images in comparison to C-band SNT1 was also reported by Bayramov et al [33] and Morishita et al [54]. According to Morishita et al [54], one of the reasons why the coherence for the C-band is higher than the X-band is the lower resolution of the C-band.…”
Section: Discussionsupporting
confidence: 53%
“…Therefore, it was not possible to relate detected subsidence hotspots to any kind of seismic processes. Additionally, recent studies by Bayramov et al [33] showed that the closest Tengiz oilfield at the coast of the Caspian Sea was subsiding because of man-made oil extraction and injection activities rather than seismicity. Based on the map of the Caspian Sea faults adapted from Levin et al [34], it was possible to observe that the Kashagan Field is located near a fault that might be subject to possible future activations either because of tectonic and seismic processes or man-made extraction of oil and gas resources (Figure 2h).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Sentinel-1 acquires up to 2000 SAR images daily, with a data capacity of even 10 TB [19], [20]. In this context, more and more scholars are using MTInSAR technology and Sentienl-1 data to carry out high-precision seismic deformation studies [21], [22], [23]. Due to the extensive range of ground deformation information, good continuity, and high deformation accuracy obtained by MTInSAR technology, the results of fault geometry parameter inversion and sliding distribution inversion are more comprehensive, detailed, and reliable [24], [25].…”
Section: Introductionmentioning
confidence: 99%